Development of Hepatocyte‐like Cell Derived from Human Induced Pluripotent Stem cell as a Host for Clinically Isolated Hepatitis C Virus. (14th August 2017) - Sa‐ngiamsuntorn, Khanit; Hongeng, Suradej; Wongkajornsilp, Adisak
Abstract: This unit describes protocols to develop hepatocyte‐like cells (HLCs) starting from mesenchymal stem cells (MSCs) as a natural host for hepatitis C virus (HCV). These include the preparation of MSCs from bone marrow, the reprogramming of MSCs into induced pluripotent stem cells (iPSCs), and the differentiation of iPSCs into HLCs. This unit also incorporates the characterization of the resulting cells at each stage. Another section entails the preparations of HCV. The sources of HCV are either the clinically isolated HCV (HCVser) and the conventional JFH‐1 genotype. The last section is the infection protocol coupled with the measurement of viral titer. © 2017 by John Wiley & Sons, Inc.